Public sector foodgrain storage losses in Bangladesh: An assessment of current losses and the identification of solutions to reduce them - Rashid, Shahidur; Kabir, Razin (International Food Policy Research Institute, 2021)
Bangladesh has a long history of catering to the consumption needs of its population through public distribution of food-grains—rice and wheat—stored across an extensive network of warehouses all over the country. This network has its roots in the Bengal famine, but now performs a variety of functions ranging from price support to providing a safety net against crises. However, the storage infrastructure is old, with many warehouses having originated some sixty years ago. The food security situation in Bangladesh has also improved remarkably from the time when this warehousing network was established. Finally, there have been remarkable improve-ments in both technology and management of grain storage that have increased overall efficiency.